FAKTOR YANG MEMPENGARUHI KEPESERTAAN JAMINAN KESEHATAN NASIONAL DI KABUPATEN - Yosalli; Firdaus Hafidz As Shidieq (Departemen Kebijakan dan Manajemen Kesehatan, Fakultas Kedokteran, Kesehatan Masyarakat, dan Keperawatan, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2020)
Background: Health insurance membership is one of three aspects of WHO’s Universal Health Coverage (UHC). Indonesia is oneof the countries in Asia that has not yet reached the UHC target.For example, DI Yogyakarta (DIY) has reached its JKN insurance membership target. However, one of the districts, namely Sleman,has not yet reached the target of membership. Thus, analysis is needed to determine the factors that influence.Objective: Knowing the characteristics of the community protected by JKN, getting an overview of membership trends and knowing thefactors that influence membership.Methods: This study uses quantitative research with a longitudinal research design. The analysis conducted in this study wasunivariate, chi-square test for bivariate and logistic regression for multivariate analysis. Respondents were selected by two-stagestratified sampling. The research was conducted in Sleman Regency in January-March 2020.Results: The trend of health insurance membership in the district tends to increase from each cycle. Factors affecting participationin the first cycle are age, education, type of work, marital status, population status and location of residence. In the second cycle areage, education, type of employment, marital status, population status, type of residence location and health status. In the third cycleare age, type of work, marital status, population status and health status. While for the fourth cycle are age, occupation, marital status,population status, religion, health status, and household income.Conclusion: Based on the analysis that has been done, every stakeholder have to strengthen the team work across sectoral. TheJKN membership should be a pre requirements for the people that had a plan to stay in Sleman Regency for study or working. The religion organization should be involved to spread the information that how important health insurance is.